Fresh Crab Plays an Important Role as a Nutrient Reservoir for the Rapid Propagation of Vibrio vulnificus - Kim, Suyeon; Chung, Han Young; Kwon, Joon-Gi; Choi, Sang Ho; Lee, Ju-Hoon (Frontiers in Microbiology, 2021)
Vibrio vulnificus is a well-known opportunistic pathogen causing food-borne illnesses by ingestion of contaminated seafood. A new strain of V. vulnificus FORC_016 was isolated from a patient’s blood sample in South Korea. The genome consists of two circular DNA chromosomes: chromosome I (3,234,424 bp with a G+C contents of 46.60% containing 2,889 ORFs, 106 tRNA genes, and 31 rRNA genes) and chromosome II (1,837,945 bp with a GC content of 47.00% containing 1,572 ORFs, 13 tRNA genes, and 3 rRNA genes). In addition, chromosome I has a super integron (SI) containing 209 ORFs, which is probably associated with various additional functions including antibiotic resistance and pathogenicity. Its pan-genome analysis with other V. vulnificus genomes revealed that core genome regions contain most of the important virulence factors. However, accessory genome regions are located in the SI region and contain unique genes regarding cell wall biosynthesis and generation of host cell protecting capsule, suggesting possible resistance ability against environmental stresses. Comparative RNA-Seq analysis of samples between contact and no contact to the crab conditions showed that expressions of amino acid/peptide and carbohydrates transport and utilization genes were down-regulated, but expressions of cell division and growth-related genes were up-regulated, suggesting that the crab may be a nutrition reservoir for rapid propagation of V. vulnificus. Therefore, consumption of the contaminated fresh crab would provide a large number of V. vulnificus to humans, which may be more dangerous. Consequently, biocontrol of V. vulnificus may be critical to ensure the safety in seafood consumption.